Index of Microcirculatory Resistance in the Assessment of Coronary Microvascular Dysfunction in Hypertrophic Cardiomyopathy - Aguiar Rosa, S (2022)
Introduction and objectives: Coronary microvascular dysfunction (CMD) is one of the most important pathophysiological features in hypertrophic cardiomyopathy (HCM). The index of microcirculatory resistance (IMR) is an invasive method to assess the coronary microcirculation. The aim was to assess CMD in patients with HCM by IMR. Methods: Adult patients with HCM without epicardial coronary artery disease underwent cardiac catheterization for the assessment of CMD by IMR (normal cut-off value ≤22.0) and coronary flow reserve (CFR) (normal cut-off value ≥2). Cardiovascular magnetic resonance (CMR) was performed to assess the ischemic burden by perfusion imaging during regadenoson-induced hyperemia, and the extent of myocardial fibrosis was assessed by late gadolinium enhancement (LGE), native T1 mapping and extracellular volume (ECV). Results: Fourteen patients were enrolled with a mean age of 62.8±6.2years, 8 (57.1%) males, of whom 9 (64.3%) had obstructive HCM. Using IMR, CMD was detected in 4 (29%) patients. Among four patients with an IMR>22.0, all had non-obstructive HCM and two had angina. CFR<2 was reported in eight patients (57%). Concordance between IMR and CFR (both normal or both abnormal) was verified in 6 patients (43%). Among four patients with IMR>22.0, perfusion defects were found in two of the three patients who underwent stress CMR. Increased ECV (>28%) was documented in two of the patients with IMR>22 and in three of the patients with IMR≤22.0. LGE was >15% in 2 of the patients with IMR>22 and in 4 with IMR≤22.0. Conclusions: IMR assessment in HCM is feasible and safe. Patients with abnormal IMR seemed to have more significant tissue abnormalities on CMR.